Penegakan Hukum Pemilu Di Indonesia Perspektif Fikih Siyasah - Muhibin; Hasani Zakiri; Akhmad Zaki Yamani (Syntax Idea)
General elections are a means of selecting a leader in Indonesia, a nation that follows a democratic system. But in reality, there is still a great deal of rasywah (bribery), the Islamic term for the purchase and sale of votes. When this happens, it's a breach of democracy, and the person responsible should face consequences. Law no. 7 of 2017 Elections, together with rules pertaining to the General Election Commission (KPU) and the Election Supervisory Body (Bawaslu), is anticipated to have the potential to decrease election-related breaches. Furthermore, positive law and siyasah fiqh both address this occurrence. Library study, in which books, statutory rules, the Al-Qur'an, Hadith, and any other relevant literature serve as the primary source of information, is what the author employs.